2008
DOI: 10.2337/dc08-0850
|View full text |Cite
|
Sign up to set email alerts
|

Association of Brominated Flame Retardants With Diabetes and Metabolic Syndrome in the U.S. Population, 2003–2004

Abstract: OBJECTIVE —Chlorinated persistent organic pollutants (POPs), endocrine disruptors accumulated in adipose tissue, were associated with diabetes and metabolic syndrome. Brominated flame retardants (BFRs), such as polybrominated diphenyl ethers (PBDEs) or polybrominated biphenyls (PBBs), are another class of POPs for which body burden is increasing. Cross-sectional associations of serum concentrations of BFRs with diabetes and metabolic syndrome were studied. RESEARCH DESIGN AND METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(126 citation statements)
references
References 20 publications
4
113
1
2
Order By: Relevance
“…A recent screen of POPs and BFRs in human serum samples, showed a significant association with diabetes and MetS with 2 (PBB-153 and PBDE-153) out of six tested BFRs (Lim et al 2008). The investigators conclude that brominated POPs stored in adipose tissue, may be involved in the pathogenesis of diabetes and MetS.…”
Section: Estrogen Receptorsmentioning
confidence: 91%
“…A recent screen of POPs and BFRs in human serum samples, showed a significant association with diabetes and MetS with 2 (PBB-153 and PBDE-153) out of six tested BFRs (Lim et al 2008). The investigators conclude that brominated POPs stored in adipose tissue, may be involved in the pathogenesis of diabetes and MetS.…”
Section: Estrogen Receptorsmentioning
confidence: 91%
“…Most of the electronic equipments recycled in the present e-waste region were produced in North America decades ago, when PBB was used as an important flame retardant. The elevated PBBs in the eggs from the e-waste recycling sites should be of concern, because of the adverse effects of these chemicals on hatchability of chicken eggs (Polin et al, 1979) and the possible toxic effects on chicken (Polin and Ringer, 1978) and human beings (Lim et al, 2008).…”
Section: Levelsmentioning
confidence: 99%
“…Lee et al (2012) reports that serum BDE-47 in the elderly is not related to abdominal obesity. However, an earlier report in Taiwan (n = 20) (Wang et al, 2008) (i.e., BDE-47 and 183) and a large-scale study (n = 1367) by Lim et al (2008) (i.e., BDE-153) both demonstrate a negative correlation between levels of PBDEs and body mass index (BMI). A study for the Center for the Health Assessment of Mothers and Children of Salinas (CHAMACOS) reveals a negative association between serum PBDE levels and child BMI collected from 7-year old Mexican-American children living in an agriculture community in California (n = 272) (Bradman et al, 2012).…”
Section: Pbdes and Human Health Effectsmentioning
confidence: 94%
“…Several epidemiological studies in the general population have strengthened the notion that PBDE exposure can induce adverse health effects (Mazdai et al, 2003;Chao et al, 2007;Main et al, 2007;Herbstman et al, 2008;Lim et al, 2008;Turyk et al, 2008;Turyk et al, 2009;Chao et al, 2010bChao et al, , 2011Gascon et al, 2012;Shy et al, 2012). There was a non-significant association of ΣPBDEs with diabetes in three studies (Lim et al, 2008;Turyk et al, 2009;Lee et al, 2011), while Lim et al (2008) found that BDE-153 shows an inverted U-shaped association with metabolic syndrome. Lee et al (2012) reports that serum BDE-47 in the elderly is not related to abdominal obesity.…”
Section: Pbdes and Human Health Effectsmentioning
confidence: 99%